IMPLIKASI PUTUSAN NOMOR 26/PUU-XI/2013 MENGENAI JUDICIAL REVIEW PASAL 16 UNDANG-UNDANG NOMOR 18 TAHUN 2003 TENTANG ADVOKAT TERHADAP PERLINDUNGAN HUKUM PROFESI ADVOKAT - Desika Ermawati Putri, Ni Made; Tjatrayasa, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
Based on the decision of the constitusional Court Number 26 / PqUU-XI / 2013 currently Advocate can not be prosecuted either civil or criminal in performing professional duties in good faith in the interests of the defense of clients in and outside the court. Article 16 of Law Number 18 of 2003 on Advocate declared contrary to Article 28 D subsection (1), Article 28 G subsection (1) and article 28 H subsection (2) of the Republic of Indonesia Constitusional 1945, and Article 16 of the Law Number 18 of 2003 on Advocate do not have binding force to the extent not understood, ”Advocate can not be prosecuted either civil or criminal in performing professional duties in good faith in the interests of the defense of clients in and outside the court”. By using the method of writing normative, this paper will discuss the implications of the decision number 26 / PUU-XI / 2013 regarding judicial review of Article 16 of Law Number 18 of 2003 on advocate the legal protection profession Advocate in and outside the court.
Keywords: advocate, legal protection